Influence of the Temperature Ramping Rate on the Performance of Vapor Transport Deposited SnS Thin-Film Solar Cells - Lee, Hyo Seok; Cho, Jae Yu; Nandi, Raju; Pawar, Pravin S.; Neerugatti, KrishnaRao Eswar; Mai, Cuc Thi Kim; Lee, Doh-Kwon; Heo, Jaeyeong (AMER CHEMICAL SOC, 2020)
The effect of the temperature ramping rate of vapor transport deposition (VTD) on the morphology, crystallinity, and orientation of SnS-absorber layers and their impact on SnS/CdS heterojunction thin-film solar cells (TFSCs) has been investigated. The SnS-absorber layers were deposited on SLG/Mo by using the VTD process at an evaporation temperature of 600 degrees C achieved by different temperature ramping rates ranging from 5 to 20 degrees C min(-1). The SnSabsorber layers deposited at a low temperature ramping rate of 5 degrees C min(-1) displayed a nonuniform size distribution of crystallites with a (111) preferred orientation. An increase in the temperature ramping rate to 20 degrees C min(-1) led to a densely packed morphology with pronounced (120)-oriented films and a more uniformly distributed grains. Furthermore, this improvement in the morphology and orientation of SnS absorbers resulted in a pronounced improvement in the diode characteristics of the heterojunction TFSC with device configuration of SLG/Mo/SnS/CdS/i-ZnO/Al-doped ZnO/Al, as revealed by current density-voltage analysis conducted under dark conditions. Consequently, the power conversion efficiency of the solar cells (active area = 0.3 cm(2)) was increased to 3.98% together with an open-circuit voltage of 0.34 V, short-circuit current density of 20.16 mA cm(-2), and fill factor of 0.58 for the TFSC fabricated with the SnS-absorber layers deposited at an elevated temperature ramping rate of 20 degrees C min(-1) compared with 2.45% for the absorber layer deposited at a ramping rate of 5 degrees C min(-1) The enhanced device performance was essentially attributed to the remarkably improved fill factor arising from the improved shunt properties of the SnS absorber.